Asiatic acid in anticancer effects: emerging roles and mechanisms - Chen, Rong; Zhang, Wan; Zhang, Meizhi; Liu, Weidong; Feng, Weike; Zhang, Yanan (Frontiers in Pharmacology, 2025)
Medicinal plants are crucial in the comprehensive treatment of anti-tumor with the advantages of high efficacy, low toxicity, multiple pathways and multi-targets synergy, leading to be a focal point of study for many oncologists. Identifying effective monomer components with anti-tumor properties from medicinal plants has long been a crucial focus in the study and development of traditional Chinese medicine. This endeavor has significant research value and promising possibilities for further advancement. Asiatic Acid (AA), a pentacyclic triterpenoid derived from Centella asiatica (L.) Urb, is used in traditional Chinese medicine and has been shown to have anti-tumor properties on a range of tumor types. The present study assessed the anti-tumor properties of AA from five different perspectives: inhibiting proliferation, inducing apoptosis, inhibiting invasion and metastasis, regulating cell autophagy, enhancing the resistance of tumor cells to drugs, and minimizing adverse side effects.